Sleep in neurointensive care patients, and patients after brain tumor surgery. - Lena Nyholm; Maria Zetterling; Kristin Elf (PLoS ONE, 2023)
Background Severely brain injured patients treated in the neuro intensive care unit (NICU) are usually sedated. Sedation may affect not only the ability to sleep, but also the EEG rhythms used to identify sleep. Aim The aims were: To study if sleep patterns could be identified in the severely brain injured and sedated patients in the NICUTo study if sleep patterns could be identified in patients the night after brain tumor surgery in the neurointermediate care unit (NIMCU)To search for risk factors for not being able to sleep after brain tumor surgery. Study design Two populations were included; one with patients affected by severe brain injury and one with patients who had undergone planned brain tumor surgery. This was a quantitative observational study using EEG. Eligible neurointensive care patients for this study had to be suffering from a neurosurgical condition (for example subarachnoid haemorrhage, acute subdural hematoma, intracerebral haemorrhage and meningitis), have affected consciousness and age over 18 years. Thirty-seven patients were included from NICU. Ninety-eight patients, with a suspected glioma (WHO grade II-IV) planned for surgery were also included. Results Neuro intensive care patients, sedated and treated in ventilator, showed no EEG sleep patterns at all. After brain tumor surgery, sleep occurred in 74% of the patients, despite frequent wake-up tests. The patients with sleep patterns were on average 8 years younger, p = 0.03. Conclusions Patients with severe brain injury are at risk of having no sleep when treated at the NICU, whereas after brain tumor surgery, sleep occurs in three-fourths of the patients. Further studies and new methods are warranted to identify sleep and investigate how the loss of sleep affects these patients and how sleep disturbances can be managed.